The soy-derived peptide Vglycin inhibits the growth of colon cancer cells in vitro and in vivo - Gao, Chang; Sun, Rui; Xie, Ya-Rong; Jiang, An-Li; Lin, Mei; Li, Min; Chen, Zheng-Wang; Zhang, Ping; Jin, Honglin; Feng, Jue-Ping (Experimental biology and medicine (Maywood, N.J.), 2017)
Vglycin, a novel natural polypeptide isolated from pea seeds, possesses antidiabetic properties. Our previous studies have shown that Vglycin can induce the differentiation of human colon adenocarcinoma cells. We aimed to determine the anticancer activity of Vglycin against colon cancer cells and to elucidate related apoptosis-inducing mechanisms. Treatment with purified Vglycin significantly reduced growth, viability, and colony formation of CT-26, SW480, and NCL-H716 colon cancer cells in a dose-dependent manner while down-regulating the expression of proliferating cell nuclear antigen. Mouse xenograft studies showed a 38% inhibition of colon cancer growth in mice treated with Vglycin (20 mg/kg/day) at day 21. Furthermore, the potential mechanisms involved in Vglycin-induced cell apoptosis were examined using cell cycle studies, ultrastructural examination, as well as apoptosis-associated pathway analysis. The results showed that Vglycin significantly promoted apoptosis and G1/S phase cell cycle arrest. As revealed by Western blot, the expression of CDK2 and Cyclin D1 was down-regulated in all three Vglycin-treated colon cancer cells, indicating that the CDK2/Cyclin D1 cell cycle pathway involved in the initiation and progression of colon cancer. Moreover, the inhibition of Vglycin-induced cell proliferation in colon cancer cells was accompanied by alteration of the expression levels of the apoptosis-related proteins Bax, Bcl-2 and Mcl-1, and an increase of caspase-3 activity. Together, our results suggest that Vglycin may be another plant-derived peptide that suppresses colon cancer, supporting the continued investigation of Vglycin as therapeutic agent for colon cancer.